The curious activity in the nucleus of NGC 4151: jet interaction causing variability?. Issue 3 (4th May 2020) - Williams, D R A; Baldi, R D; McHardy, I M; Beswick, R J; Panessa, F; May, D; Moldón, J; Argo, M K; Bruni, G; Dullo, B T; Knapen, J H; Brinks, E; et al.
ABSTRACT: A key characteristic of many active galactic nuclei (AGNs) is their variability, but its origin is poorly understood, especially in the radio domain. Williams et al. (2017) reported a ∼50 per cent increase in peak flux density of the AGN in the Seyfert galaxy NGC 4151 at 1.5 GHz with the e-MERLIN array. We present new high-resolution e-MERLIN observations at 5 GHz and compare these to archival MERLIN observations to investigate the reported variability. Our new observations allow us to probe the nuclear region at a factor three times higher resolution than the previous e-MERLIN study. We separate the core component, C4, into three separate components: C4W, C4E, and X. The AGN is thought to reside in component C4W, but this component has remained constant between epochs within uncertainties. However, we find that the Eastern-most component, C4E, has increased in peak flux density from 19.35 ± 1.10 to 37.09 ± 1.86 mJy beam −1, representing an 8.2σ increase on the MERLIN observations. We attribute this peak flux density increase to continue interaction between the jet and the emission line region (ELR), observed for the first time in a low-luminosity AGNs such as NGC 4151. We identify discrete resolved components at 5 GHz along the jet axis, which we interpret as areas of jet–ELR interaction.